Foreign Policy Concept of Gerhard Schroeder in the Field of Security in the Middle East - E. Y. Dobizha (Научный диалог, 2017)
The article is devoted to stages of modern German policy in the Middle East and examines Chancellor G. Schroeder’s foreign policy agenda for the region. It is emphasized that in the new conditions of a changed world order Chancellor G. Schroeder had to build a foreign policy strategy in the Middle East region, basing on the common European course and considering significant role of the Euro-Atlantic partnership. The basic military strategy of Germany are formulated. The amount of Germany economic and military aid is specified. The main controversies between the Federal government and Washington are mentioned on the question of the volume of German investments in joint action in the region and military involvement of Germany. The author shows the willingness and desire of Germany to act as European leader in the construction of European security system. The question is raised about the fact that today the problem of international terrorism and violations of human rights in the developing countries of the Middle East is one of the global problems of modernity and Germany considers these areas are among the priorities in its foreign policy strategy in the region.